Implementation of Islamic Religious Education in Shaping Students' Morals at Muhammadiyah PK Surakarta High School - Dzakiy Arribath; Mohamad Ali (Dinasti International Journal of Education Management And Social Science, 2024)
Morals are very important to be taught to students to shape their behavior so that they can blend in with society well. This research aims to find out how the implementation of Islamic Religious Education in shaping morals at Muhammadiyah PK Surakarta High School. The method in this research uses a qualitative method with a field study approach. The research technique used is to use data triangulation that combines observation, interviews and documentation. The results showed that the learning of PAI at SMA Muhammdiyah PK Surakarta was quite good as seen from students who had behaved well although some were not in accordance with what was expected. Although the implementation of PAI learning on student morals at SMA Muhammadiyah PK Surakarta is quite good, it has not achieved maximum results as expected. This is due to the limited time allocation for Islamic Education subjects compared to other general subjects. Other inhibiting factors include students' unfavorable backgrounds, unsupportive social environments, lack of facilities and infrastructure, and the influence of mass media such as television and print media.